PENGARUH KEPEMIMPINAN, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT DELAPAN JAYA PERKASA GARMEN KABUPATEN SRAGEN - Murdani, Farizal; Danarwati, Yanti Sri (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2024)
This study aims to determine the effect of leadership, work motivation, and work environment on the performance of employees of PT. Delapan Jaya Perkasa Garmen Kabupaten Sragen, either partially or simultaneously. This research is a quantitative research. The sampling technique used was Proportionate stratified random sampling with purposive sampling by taking primary data and secondary data provided by the company. The population of this research is 200 employees where 70 employees are the sample. The analysis technique used is descriptive statistics, hypothesis testing, classical assumption test, multiple linear regression analysis, and the coefficient of determination (R²). Allegedly leadership, work motivation and work environment on the performance of employees of PT. Delapan Jaya Perkasa Garmen Kabupaten Sragen, either in part or in part simultaneously. The data needed in this study is primary data obtained from questionnaires distributed to respondents. Data results analysis in this study it can be concluded that leadership, work motivation, and work environment on the performance of employees of PT. Delapan Jaya Perkasa Garmen Kabupaten Sragen, either in part or in part simultaneously. These things show that the greater the influence of leadership, the better in providing work motivation and paying attention to the work environment, the higher the level of employee performance. People will trust companies that always pay attention to human resources.